SISTEM INFORMASI AKUNTANSI ARUS KAS PADA DINAS PERHUBUNGAN KABUPATEN KENDAL MENGGUNAKAN METODE ACCRUAL BASIS - M Munifah; Edy Siswanto; Tedy Wahyu Pramuditya (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
The financial recording system at the Kendal Department of Transportation is still using a manual system, meaning that all transaction activities that occur are only written in bookkeeping, and do not yet have a special application used in data processing and financial reporting. Prone to cause loss of transaction data thus hampering the reporting process. In addition, it is difficult to find financial data on cash receipts and disbursements due to the unavailability of an accessible web-based financial information system. The Kendal Regency Transportation Office needs an application that can be used in data processing and financial statement presentation and displays financial reports quickly, effectively and efficiently when needed and makes it easier to obtain financial information at the Kendal Regency Transportation Office. The application of a cash flow accounting information system at the Kendal Regency Transportation Office has achieved the desired goal, namely to simplify the process of recording cash financial transactions so that the use of cash management time is more efficient and presents financial reports of income, expenses and cash flows quickly, precisely and accurately.